The Effects of Capital Intensity and Good Corporate Governance on Tax Avoidance with Firm Size as A Moderating Variable - Nida Ul Husna; Gemi Ruwanti; Saifhul Anuar Syahdan; Soelistijono Boedi (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2026)
This study aims to analyse and empirically examine the effects of capital intensity and good corporate governance on tax avoidance in energy sector companies listed on the Indonesia Stock Exchange, with firm size as a moderating variable. This study uses a quantitative approach and secondary data obtained from the annual financial reports of energy sector companies for the 2021-2024 period. The sample was selected using purposive sampling. Based on the sampling criteria, 34 companies were selected as the research sample. The data were analysed using multiple linear regression and moderated regression. The results show that capital intensity has a significant effect on tax avoidance, whereas good corporate governance does not. The moderation test indicates that firm size does not moderate the effect of capital intensity on tax avoidance, but does moderate the effect of good corporate governance on tax avoidance. These findings indicate that fixed asset investment plays an important role in corporate tax strategies, while the effectiveness of institutional monitoring in controlling tax avoidance depends on firm size